A Post-Supersessionist Reading of the Temple and Torah in Mark’s Gospel: The Parable of the Vineyard - Vered Hillel (Religions, 2023)
Most interpretations of the Temple and Torah in the Gospel of Mark have held a negative view toward the Jewish institutions, declaring that the old has been replaced by the new, meaning Jesus is the new Temple and the Church has replaced the Jewish people. This article presents a post-supersessionist reading of the Temple and Torah in Mark’s Gospel, focusing on the Parable of the Vineyard (Mk 12:1–12) in the broader narrative context (11:1—13:1) and the canonical narrative, thereby maintaining the Gospel’s connection with the Jewish people and their covenant relationship with God. These two contexts frame the parable and set parameters for its interpretation, thereby preventing anti-Torah and anti-Temple interpretations and the theological belief that Christians are Abraham’s true and rightful heirs.